2006
DOI: 10.1002/jts.20118
|View full text |Cite
|
Sign up to set email alerts
|

Panic reactions to terrorist attacks and probable posttraumatic stress disorder in adolescents

Abstract: A number of factors, including subjective reactions and appraisal of danger, influence one's reaction to a traumatic event. This study used telephone survey methodology to examine adolescent and parent reactions to the 2001 World Trade Center attacks 6 to 9 months after they occurred. The prevalence of probable posttraumatic stress disorder (PTSD) in adolescents was 12.6%; 26.2% met study criteria for probable subthreshold PTSD. A probable peri-event panic attack in adolescents was strongly associated with sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
44
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(48 citation statements)
references
References 37 publications
(41 reference statements)
4
44
0
Order By: Relevance
“…The prevalence of PTSD in adolescents was 12.6% and an additional 26% met criteria for probable PTSD. A strong correlation was found between probable panic attacks in the initial stages of the disaster and the development of probable PTSD subsequently (Pfefferbaum et al 2006a).…”
Section: Impact On Children and Adolescentsmentioning
confidence: 84%
“…The prevalence of PTSD in adolescents was 12.6% and an additional 26% met criteria for probable PTSD. A strong correlation was found between probable panic attacks in the initial stages of the disaster and the development of probable PTSD subsequently (Pfefferbaum et al 2006a).…”
Section: Impact On Children and Adolescentsmentioning
confidence: 84%
“…Those who met Criterion A as well as meeting criteria in two of the three B, C, and D categories were "partial PTSD diagnosis likely." This procedure was employed by Pfefferbaum and colleagues (Pfefferbaum, Stuber, Galea & Fairbrother, 2006) in their study of PTSD after the terrorist attacks on the World Trade Center. The PTSD Reaction Index has good psychometric properties (Steinberg et al, 2004) and has been used in Taiwan in several studies (Chen et al, 2002;Chen & Wu, 2006).…”
Section: Methodsmentioning
confidence: 99%
“…From the NCS-R data, Kessler et al [47] reported 45.0% comorbidity with other anxiety disorders in their PA-only group (i.e., PAs without a history of PD or agoraphobia), with highest comorbidity rates for specific phobia (21.0%) and social phobia (18.8%). Other studies have suggested that the presence of panic symptoms at the time of a traumatic event (i.e., a ''cued'' PA in response to trauma) may be associated with higher rates of an ensuing acute stress disorder [48,49] or posttraumatic stress disorder [50][51][52] compared to individuals who do not show panic symptomatology at trauma. As discussed by, [48] the association of PAs and acute stress disorder may be explained by an overlap in their symptomatology (e.g., derealization, fear of dying), a common predisposition to develop both conditions, and PAs intensifying the level of stress during the traumatic event.…”
Section: Comorbiditymentioning
confidence: 96%